HLA class II variants defined by next generation sequencing are associated with sarcoidosis in Korean patients - Sikorová, Kateřina; Moon, Su-Jin; Yoon, Hee-Young; Strnad, Adam; Song, Jin Woo; Petrek, Martin (Scientific reports, 2022)
Polymorphic genes with immune functions, namely those of the human leukocyte antigen (HLA) system, have been implicated in sarcoidosis pathogenesis. As HLA polymorphisms in sarcoidosis have not been yet investigated in the Korean population, we used next-generation sequencing (NGS), allowing detailed characterization of HLA alleles to investigate the role of HLA variation in Korean sarcoidosis patients. We enrolled 103 patients diagnosed by the ATS/ERS/WASOG guidelines at Asan Medical Centre, Seoul, Korea. Among those, genotyping of 7 HLA loci (HLA-A, -B, -C, -DQA1, -DQB1, -DRB1, -DPB1) was performed using Omixon HolotypeTM kit and HLATwin softwareTM. HLA allele frequencies were compared with frequency data on healthy Koreans from the allelic frequency databases, and 4-digit characteristics of HLA genotyping were used. Associations were assessed by two-tailed Fischer's exact test with correction for multiple comparisons. Variants previously associated with sarcoidosis risk (HLA-C*03:04, HLA-DRB1*12:01, HLA-DRB1*14:54) and a known protective variant HLA-DPB1*04:01, were associated with sarcoidosis in Koreans. Further, we suggest new HLA variants associated with sarcoidosis risk (e.g., HLA-DQA1*05:08) and novel protective variants HLA-DQB1*03:02 and HLA-DQA1*01:02 in Koreans. This first study of HLA variation in Korean patients with sarcoidosis by precise genotyping methodology reports data that could serve future meta-analyses on HLA variation's role in sarcoidosis.
Keywords: alely; frekvence genu; MHC antigeny I. třídy; High-Throughput Nucleotide Sequencing; Alleles; HLA-DRB1 Chains; Gene Frequency; lidé; haplotypy; Sarcoidosis; sarkoidóza; Histocompatibility Antigens Class I; HLA-DRB1 řetězec; Haplotypes; vysoce účinné nukleotidové sekvenování; Humans